Suspected Transfusion Related Acute Lung Injury Improving following Administration of Tranexamic Acid: A Case Report - Stan Ryniak; Piotr Harbut; Anders Östlund; Andrzej Mysiak; Jan G. Jakobsson (Case Reports in Anesthesiology)
A 16-year-old woman with craniofacial injury developed severe acute respiratory failure under the primary reconstructive surgical procedure requiring several units of blood and plasma. A transfusion related acute lung injury (TRALI) was suspected and supportive treatment was initiated. Because of the severity of symptoms, acute extracorporeal membrane oxygenation (ECMO) was planned. During preparation for ECMO, a single intravenous dose, 1 g of tranexamic acid, was administered and a remarkable improvement was observed shortly thereafter. The patient was placed on ECMO for 16 hours. The further course was uncomplicated and the patient was discharged from ICU on the 6th day after admission fully and she recovered. A clinical improvement was observed in a timely fashion following the administration of tranexamic acid. The handling of a suspected TRALI and potential benefit from administration of tranexamic acid are discussed in this case report.